Zircon U-Pb-Hf isotopes and geochemistry of Jurassic igneous rocks from the southern Zhangguangcai Range, NE China: constraints on magmatism, petrogenesis and tectonic implications. Issue 16 (1st November 2020) - Han, Zuo-Zhen; Ren, Xiang; Schertl, Hans-Peter; Li, Xu-Ping; Song, Zhi-Gang; Du, Qing-Xiang; Han, Chao; Zhong, Wen-Jian; Gao, Li-Hua
ABSTRACT: In this study, we present new zircon U-Pb and Hf isotope data and geochemical analyses for Jurassic igneous rocks from the southern Zhangguangcai Range, NE China. In the context of our new U/Pb data together with other published data (n = 165), we recognize three major magmatic pulses in the eastern Songnen Block during the Jurassic: earliest Jurassic (200–195 Ma), late Early Jurassic (183–175 Ma) and early Late Jurassic (ca. 163 Ma). According to the petrological classification scheme, rocks are divided into two categories of andesite and I-type granitoids. Generally, Early Jurassic monzogranites have more evolved compositions with SiO2, Al2 O3, and K2 O+Na2 O concentrations of 67–74 wt.%, 13.28–17.04 wt.% and 7.25–9.31 wt.%, respectively than Late Jurassic granodiorite. Early Jurassic andesite has SiO2, Al2 O3, Na2 O+K2 O contents of 54.64–56 wt.%, 17.27–17.44 wt.% and 3.47–4.06 wt.%, respectively with low Mg# values of 0.18–0.26. In addition, all samples show enrichment in light rare earth elements (LREEs) and large-ion lithophile elements (LILEs) but depletion in high strength field elements (HSFEs, such as Nb, Ta, P and Ti) and low Sr/Y and (La/Yb)N ratios, all of which are characteristic of arc-type magmatic signatures. In view of the Hf isotope signatures, these rocks show high initial 176 Hf/ 177 Hf ratios (0.282711–0.283069) corresponding to positive εHf (t) values (+0.39 to +13.66) and Neoproterozoic two-stage model ages (1154–550 Ma). In summary, the geochemical results suggest that the primary magmas of Jurassic granitoids were derived from variable degrees of partial melting of juvenile lower crust, whereas Early Jurassic andesite was derived from the partial melting of mantle wedge peridotite metasomatized by hydrous melts from subducting sediments and/or oceanic crust. The Jurassic arc-type magmatism in the eastern Songnen Block indicates that the Mudanjiang oceanic plate was still subducting in the Jurassic. Graphical abstract: uf0001